BULLYING DITINJAU DARI PSYCHOLOGICAL WELL-BEING PADA MAHASISWA KORBAN BULLYING DI UNIVERSITAS NASIONAL KARANGTURI SEMARANG - Ivana Dwi Susanto; Qurnia Fitriyatinur (IMAGE, 2024)
This research aims to examine the relationship between bullying and psychological well-being using a quantitative approach. The data in this research was obtained from filling out questionnaires by 50 students at Karangturi National University, Semarang. The research data was then analyzed using the Spearman Rank correlation analysis technique with the help of the SPSS version 26 program. The results of the research showed that the sig (2-tailed) correlation test value was -0.755 (p < 0.05) which indicated that the bullying variable had a relationship. significant negative with the psychological well-being variable, meaning that high levels of bullying behavior pose a risk of reducing students' psychological well-being . Thus, (Ho) the proposed hypothesis is accepted, namely that there is a negative relationship between bullying and psychological well-being in student victims of bullying at Karangturi National University, Semarang. Keywords : bullying, psychological well-being , victims, relationships